Public Libraries Encouraged to Meet the Health Information Needs of Tribal Women in Bangladesh - Luo, Lili (Evidence Based Library and Information Practice, 2024)
A Review of: Yesmin, S., Abdul Karim, M., & Atikuzzaman, M. (2023). Community engagement of public libraries for ensuring tribal women’s health literacy in Bangladesh. IFLA Journal, 49(4), 678–693. https://doi.org/10.1177/03400352231198260 Objective – To investigate public libraries’ existing community engagement practices, explore their willingness to provide health information services to tribal communities in Bangladesh, and examine tribal women’s health information-seeking behavior and interest in obtaining health information from public libraries. Design – A cross-sectional study using online interviews and structured questionnaires. Setting – Public libraries and tribal communities in tribal regions of Bangladesh. Subjects – Public librarians (n=11) and tribal women (n=276) from three tribal districts in Bangladesh (Bandarban, Khagrachari, and Mymensingh). Methods – Interviews were conducted with librarians via Zoom in January 2023. Survey questionnaires were distributed to a convenience sample of 300 tribal women from February to March 2023. Data was analyzed in the Statistical Package for the Social Sciences (SPSS), using univariate and bi-variate measures. Main Results – All of the libraries provided print materials (books, newspapers, and periodicals) for reading and lending and offered photocopying and Internet browsing services. Other forms of resources such as microfiches and digital materials, inter-library loan services, and facilities for people with disabilities were not widely available. Most libraries (72.8%) did not provide any specific program (e.g., health-related outreach program) for tribal community engagement, although they all recognized the urgency and value of such programs. Lack of funding and bureaucratic complexities were identified as the top two barriers. Out of the 276 tribal women responding to the survey, close to two-thirds of the respondents indicated they were either moderately or very interested in receiving health information. The top three health topics the respondents sought information on were vaccinations, symptoms of disease, and nutrition. The primary health information sources for the respondents were doctors at nearby community clinics or government hospitals, and none of the respondents sought health information from public libraries. Most respondents acknowledged the importance of being informed about health issues and found it difficult to locate health information on the Internet. High costs and lack of awareness regarding health issues represented the main challenges the respondents encountered when seeking health information. Among the demographic variables, respondents’ religion and age were negatively correlated with their interest in health information, while their education status was positively correlated with it. Conclusion – Public libraries in tribal areas in Bangladesh lacked health information services but recognized the importance of providing them. Tribal women expressed interest in receiving health information, encouraging public libraries to develop and implement related services and programs. Public libraries may consider adding new job titles such as consumer health librarians and partner with other stakeholders for better community engagement. The government of Bangladesh should substantially invest in public libraries as community hubs and minimize bureaucratic hurdles that prevent public libraries from initiating new services. Professional library organizations in Bangladesh may also draw ideas from the study in establishing professional guidelines for health information services and community outreach programs.